2021
DOI: 10.1007/s00429-020-02206-3
|View full text |Cite
|
Sign up to set email alerts
|

Quail-chick grafting experiments corroborate that Tbr1-positive eminential prethalamic neurons migrate along three streams into hypothalamus, subpallium and septocommissural areas

Abstract: The prethalamic eminence (PThE), a diencephalic caudal neighbor of the telencephalon and alar hypothalamus, is frequently described in mammals and birds as a transient embryonic structure, undetectable in the adult brain. Based on descriptive developmental analysis of Tbr1 gene brain expression in chick embryos, we previously reported that three migratory cellular streams exit the PThE rostralward, targeting multiple sites in the hypothalamus, subpallium and septocommissural area, where eminential cells form d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 85 publications
2
11
0
Order By: Relevance
“…A comparison of Sim1 with Foxg1 shows that this area contains Sim1/Foxg1 double-labeled and Sim1 single-labeled cells (present results), indicating an external origin of at least some of the cells of this corridor. Moreover, this ample area also contains Otp cells (part of them coexpressing Foxg1, as noted in the results) and other cell types with different molecular profiles and apparent origins, such as those with Lhx5 and Tbr1 derived from the prethalamic eminence (PThE) and those with Lhx9 of pallial origin (as discussed previously by Abellán et al, 2009 ; see also Abellán and Medina, 2009 ; Abellán et al, 2010 ; Vicario et al, 2017 ; Alonso et al, 2020 , 2021 ). The LOT of mice also appears to include a variety of cell subtypes with different molecular profiles and embryonic origins (discussed by García-López et al, 2008 , Garcia-Calero et al, 2021 ).…”
Section: Discussionsupporting
confidence: 68%
“…A comparison of Sim1 with Foxg1 shows that this area contains Sim1/Foxg1 double-labeled and Sim1 single-labeled cells (present results), indicating an external origin of at least some of the cells of this corridor. Moreover, this ample area also contains Otp cells (part of them coexpressing Foxg1, as noted in the results) and other cell types with different molecular profiles and apparent origins, such as those with Lhx5 and Tbr1 derived from the prethalamic eminence (PThE) and those with Lhx9 of pallial origin (as discussed previously by Abellán et al, 2009 ; see also Abellán and Medina, 2009 ; Abellán et al, 2010 ; Vicario et al, 2017 ; Alonso et al, 2020 , 2021 ). The LOT of mice also appears to include a variety of cell subtypes with different molecular profiles and embryonic origins (discussed by García-López et al, 2008 , Garcia-Calero et al, 2021 ).…”
Section: Discussionsupporting
confidence: 68%
“…Recently, it has exhaustively been studied based on the analysis of the marker Tbr1, expressed in mouse and chicken at early and late developing stages [Alonso et al, 2020[Alonso et al, , 2021, as it has been demonstrated in turtle [Moreno et al, 2012], lizard [Desfilis et al, 2018], and Xenopus [Domínguez et al, 2015]. In chicken, three migratory cellular streams have been defined that exit the prethalamic eminence rostralward, targeting multiple sites in the hypothalamus, subpallium, and septocommissural area, where eminential cells form distinct nuclei or disperse populations [Alonso et al, 2021]. Thus, the chicken eminential derivatives seem to respect the telencephalic pallial domains, representing a significant evolutionary difference with respect to the mammalian counterparts [Alonso et al, 2021].…”
Section: The Prethalamic Eminencementioning
confidence: 99%
“…In chicken, three migratory cellular streams have been defined that exit the prethalamic eminence rostralward, targeting multiple sites in the hypothalamus, subpallium, and septocommissural area, where eminential cells form distinct nuclei or disperse populations [Alonso et al, 2021]. Thus, the chicken eminential derivatives seem to respect the telencephalic pallial domains, representing a significant evolutionary difference with respect to the mammalian counterparts [Alonso et al, 2021]. In reptiles, migratory movements similar to those described in mammals have been suggested on the basis of p73 expression in the prethalamic eminence [Cabrera-Socorro et al, 2007].…”
Section: The Prethalamic Eminencementioning
confidence: 99%
See 2 more Smart Citations